Гарри Поттер и Принц-полукровка: [роман] / Дж. К. Ролинг - Ролинг Джоан Кэтлин (Росмэн-Пресс, 2006)
Экземпляры: С/а ДБ (20140718) / Инвентарный номер: 101271 / Цена: 200.00 / Авт.знак: Р 67 / ГРНТИ: 17.82 / ББК: 84(4Вел)